(untitled) (Journal of Education and Development, 2022)
With the unceasing liberation of people’s ideology, the promotion of women’s rights has been raised to unprecedented importance in today’s society. Therefore, more and more theologists have started to re-examine the conventional Catholic doctrines through a critical lens, especially under the framework of moral philosophy. The author aims to explore two main conceptions deep-rooted in Catholic traditions or sacred books that are considered to convey gender inequality, for one decrees the inferior of the gender female to the gender male while the other emphasizes women’s obedience to men’s instructions. In addition, the author analyzes the origin of such conceptions, the dualistic theory, and how renowned Catholic feminists such as Margret Farley and Lisa Cahill managed to develop new comprehension towards Catholicism based on Catholic feminist ethics. While the modern spiritual movements are predominantly derived from Western experience, the application of theological innovations in the East-Asia region still depends on different, complex religious realities. In this article, the author takes China as an example and investigates how secularization may encourage the practice of Catholic feminist reformations in China.